PENGEMBANGAN MEDIA POP-UP BOOK BERBASIS CODING UNPLUGGED PADA MATERI NORMA KELAS V SEKOLAH DASAR - Neta Tabhita Partika; Desi Eka Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop and validate an innovative learning medium in the form of a Pop-Up Book integrated with Coding Unplugged activities for teaching norms to fifth-grade elementary school students. The background of this research is based on the continued dominance of conventional teaching methods that are less effective in actively engaging students in understanding and applying religious, social, moral, and legal norms in daily life. This study employed a Research and Development (R&D) approach using the 4D development model, which consists of the define, design, develop, and disseminate stages. The development process involved designing instructional media tailored to students’ characteristics and integrating unplugged coding activities to enhance logical thinking and collaborative skills. Data were collected using validation sheets distributed to media experts, material experts, and language experts. The results revealed that the Coding Unplugged-based Pop-Up Book achieved a validity score of 0.99, categorized as very high, covering aspects of media design, content appropriateness, and language usage. In addition, qualitative feedback from validators indicated that the media is attractive, easy to use, and capable of increasing students’ motivation and engagement in the learning process. Therefore, the developed media is considered feasible to be implemented as an interactive and innovative learning tool to improve students’ understanding of norms and to support character development in elementary school education.